Beginning App Development with Parse and PhoneGap - Alber, Stephan. (Apress : Imprint: Apress, 2015)
Beginning App Development with Parse and PhoneGap teaches you how to start app development with Parse and PhoneGap: free and open source software. Using the building block languages of the web--HTML, JavaScript, and CSS--you’ll be on your way to creating a fully working product with minimal effort as fast as possible. With over 25 years' of combined experience, the authors make daunting tasks seem trivial. There is no book on the market that can take you from designer to developer faster. Using Facebook’s Parse as backend service, and Adobe’s PhoneGap (or Cordova) as a mobile development framework, building a highly customizable application is easier than you can imagine. A basic understanding of JavaScript, HTML, and CSS is not required, but it will help you pick up concepts faster. This book is geared toward a designer who wants to explore the world of application development. If you do not know anything about design, that’s OK! We will walk you through step by step on how to build your first native iOS or Android app in the fastest and easiest way possible. Using free and open source software, this book will get you up and running quickly and efficiently--start using Parse and PhoneGap today with this key title.